Overview of Women Entrepreneurship in The Eastern Cape Province of South Africa - Donga, Gift; Chimucheka, Tendai (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This article aims to review prior research on women entrepreneurship and recommend/propose future research opportunities for South Africa’s women’s entrepreneurship research agenda. Design/methodology/approach: A literature review technique was used, and all studies between 2002 and 2022 that addressed the issues pertaining to women entrepreneurs in the Eastern Cape were searched and analysed. To successfully do this, a review of literature consisting of 14 studies was undertaken. Findings: The literature review pertaining to women entrepreneurship in the Eastern Cape Province yielded five ensuing themes: gender bias within the entrepreneurial discourse, motivation for women entrepreneurs, contribution of women entrepreneurs, barriers facing women entrepreneurs, and support required by women entrepreneurs. Research limitations/implications: Women entrepreneurship research in South Africa is still growing, which presented a limit to the number of studies that were used in carrying out the review. Practical implications: The study encourages women business owners to develop their professional skills and familiarise themselves with entrepreneurial capabilities that have a positive impact on their productivity. Paper type: Literature review